Aplikasi Sistem Pendataan Nilai Akademik Siswa Berbasis Web di SMA N 03 Lebong - Pahrizal Pahrizal; Ardi Wijaya; Eka Sahputra; Vivin Tamara (UNIVED Press, 2024)
The world of the internet is increasingly developing because humans are always looking for new breakthroughs. Web-based data collection of academic scores at SMA N 03 Lebong, especially in collecting student academic scores, starting from entering data (input), changing data and displaying data (output). Problems that can be identified from the design of an offline web-based student academic data collection system that runs at SMA N 03 Lebong include the system that has been running so far to obtain information about test scores, and manual lesson schedules. In overcoming the problem, a system is needed to handle data collection on student report cards. By using a computerized system and application design, everything can be stored neatly, integrity is guaranteed, data collection can be done quickly, precisely and accurately. The data in this study are data from SMA N 03 Lebong students. The data used in this study came from SMA N 03 Lebong. The system was built using PHP programming and MySQL Database. This system can also be accessed anywhere using a web browser connected to the internet.